Comprehensive primary health care under neo-liberalism in Australia. (November 2016) - Baum, Fran; Freeman, Toby; Sanders, David; Labonté, Ronald; Lawless, Angela; Javanparast, Sara
Abstract: This paper applies a critical analysis of the impact of neo-liberal driven management reform to examine changes in Australian primary health care (PHC) services over five years. The implementation of comprehensive approaches to primary health care (PHC) in seven services: five state-managed and two non-government organisations (NGOs) was tracked from 2009 to 2014. Two questions are addressed: 1) How did the ability of Australian PHC services to implement comprehensive PHC change over the period 2009–2014? 2) To what extent is the ability of the PHC services to implement comprehensive PHC shaped by neo-liberal health sector reform processes? The study reports on detailed tracking and observations of the changes and in-depth interviews with 63 health service managers and practitioners, and regional and central health executives. The documented changes were: in the state-managed services (although not the NGOs) less comprehensive service coverage and more focus on clinical services and integration with hospitals and much less development activity including community development, advocacy, intersectoral collaboration and attention to the social determinants. These changes were found to be associated with practices typical of neo-liberal health sector reform: considerable uncertainty, more directive managerial control, budget reductions and competitive tendering and an emphasis on outputs rather than health outcomes. We conclude that a focus on clinical service provision, while highly compatible with neo-liberal reforms, will not on its own produce the shifts in population disease patterns that would be required to reduce demand for health services and promote health. Comprehensive PHC is much better suited to that task. Highlights: Theories on neo-liberalism explain changes to comprehensive primary health care. Neo-liberal practices have reduced the comprehensiveness of primary health care. Increasing health care costs increases pressure to reduce health promotion actions. Community management encourages comprehensive primary health care. Primary health care includes disease prevention and health promotion for all.